Economic Uncertainty and the Demand for Broad Money in South Africa - Tan, Wen Hsien; Puah, Chin Hong; Wong, Shirly Siew Ling; Chong, Mei Teing (Macrothink Institute, 2020)
This paper scrutinised the impact of economic uncertainty on the broad money demand in South Africa using quarterly data from 2001 to 2018. Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model is employed to capture the volatilities of selected components in order to construct an economic uncertainty index (EUI) for South Africa. The constructed index is then used as a regressor along with real income, interest rate and exchange rate in determining South African demand for broad money. The empirical finding using the Autoregressive Distributed Lag approach notably shows that the EUI is negatively affecting South Africa’s demand for broad money in the long term. This reveals that economic agents tend to hold real or safer assets than riskier assets, thus reduce broad money demand during times of heightened economy in South Africa. The model is cointegrated in the long-run and stable with the inclusion of EUI in the broad money demand function for South Africa. The findings are able to assist policy makers in using suitable determinants as stabilisation tools and targeting a more effective monetary policy framework refined by appropriate monetary aggregates in South Africa.